Teaching Students to Think Creatively Through Independent Education in Higher Education - Dilorom Abdullayeva; Bakhtiyor Aminov; Nilufar Xodjayeva (Research Parks Publishers, 2021)
The success of group work depends on the teacher's ability to organize learning activities. That is, the ability of the teacher to organize the individual activities of each student in the group, each student to receive the support of the teacher, depends on the progress of the work and the success of the final result. There are a number of shortcomings in the organization of group work. One of the challenges is to be able to form groups with the right goals and organize work in them